Peran Guru dalam Meningkatkan Keterampilan dan Sikap Kedisiplinan Siswa dalam Kegiatan Belajar Mengajar di SD Al Ma’soem - Kinesti, Rakanita Dyah Ayu; Taqiya, Nadifa; Nisak, Lailiya Hikmatun; Pionika, Rema Vina; Praharsini, Adiba; Laela, Rohmah Nur (Lembaga Yasin AlSys, 2021)
Al-Ma'soem is a large pesantren-based educational foundation that provides and applies conceptual discipline to its students and does not make it a burden for its students. So, if there is a violation then he must bear the consequences of sanctions in the form of weight points. In increasing students' creativity in learning, teachers need to pay attention to several things: providing opportunities for students to choose a topic that will be done in solving a problem, it is necessary to involve students in providing an assessment of their work, and the teacher gives gifts or awards. The teacher's way of mastering the learning atmosphere in the classroom is that the teacher must create and manage learning as effectively as possible so that students are comfortable with the learning process, and make the learning process not boring. This study aims to gain knowledge about how teachers improve student discipline, the role of teachers in improving students' skills/creativity, and how teachers master the learning atmosphere in the classroom. This data retrieval the author uses the method of non-participation observation, question and answer and documentation. The conclusion of this study is that discipline at Al Ma'soem Elementary School is in the form of point weights, in increasing students' creativity in learning the teacher is tasked with evaluating assignments, attitudes and behavior of students who are not good, and how the teacher masters the learning atmosphere in the classroom by creating and managing learning that is effective so that students feel comfortable and not bored.